2018
DOI: 10.1038/s41598-018-34389-5
|View full text |Cite
|
Sign up to set email alerts
|

Two novel, putative mechanisms of action for citalopram-induced platelet inhibition

Abstract: Citalopram, a selective serotonin reuptake inhibitor (SSRI), inhibits platelet function in vitro. We have previously shown that this action is independent of citalopram’s ability to block serotonin uptake by the serotonin transporter and must therefore be mediated via distinct pharmacological mechanisms. We now report evidence for two novel and putative mechanisms of citalopram-induced platelet inhibition. Firstly, in platelets, citalopram blocked U46619-induced Rap1 activation and subsequent platelet aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…The collapse of the U46619 response at 200 µM is also consistent with this hypothesis. Preliminary data that support these hypotheses have recently been presented 48 .…”
Section: Discussionmentioning
confidence: 88%
“…The collapse of the U46619 response at 200 µM is also consistent with this hypothesis. Preliminary data that support these hypotheses have recently been presented 48 .…”
Section: Discussionmentioning
confidence: 88%
“…Together, these data suggest that R5421 may inhibit αIIbβ 3 activation by acting distal to receptor signalling, perhaps on Rap1b activation, though the precise target remains to be identified. Interestingly, CalDAG‐GEFI has been recently identified as a target of the antidepressant, citalopram (Roweth et al, 2018), indicating that it is possible for this protein to be inhibited by small molecules. Another possible target of R5421, a carbamate, is arylacetamide deacetylase‐like 1 (AADACL1), a lipid deacetylase that regulates Rap1b activity in platelets.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely not a consequence of its canonic function as an SSRI. However, citalopram has additional targets and inhibits platelet activation independent of SERT, possibly via inhibition of Rap1 activation (Roweth et al ). Interestingly, it has been reported that Rap1 deletion increases exocytosis in mouse cortical neurons, possibly by regulating calcium channel expression (Subramanian et al ).…”
Section: Discussionmentioning
confidence: 99%